Intenção de compra no social commerce : um estudo sobre a perspectiva dos consumidores brasileiros - Rios, Larissa Soares de Queiroz (2019)
The adherence of internet users to social media platforms for peer interaction, content generation and sharing has modified the forms of communication, work, relationship and entertainment of individuals, in a way that these tools are increasingly being used for differentiated purposes, including commercial reasons. In this sense, the use of social media in commercial relations works as a vehicle for the emergence of the so-called social commerce phenomenon. Social commerce associates commercial and social online activities to support consumers in the purchasing and consumption decision process of goods and services, being recognized as a second generation of electronic commerce in which the company-consumer relationship is more interactive. In the national scenario, social commerce is an emerging prospect for research into the possibilities of adoption by online consumers. Considering these facts, this study aims to verify how the social commerce components, related to social support, social presence and flow might influence the trust and, consequently, consumers' online purchase intention. Thus, an adaptation of the theoretical proposals of Hajli (2015) and Dzahaban and Shihab (2016) has been used as a research model. In order to verify the causal relationships of the proposed model, the study has assumed, in terms of methodological procedures, a quantitative nature, a descriptive and correlational approach, choosing “survey” as a research strategy. Therefore, an online questionnaire was used for data collection with 31 indicators referring to the proposed theoretical model, among other items. A non - probabilistic sample was obtained, by self - selection, of 232 Brazilian respondents, Facebook users, who search for information on social media products and are online consumers. The data were submitted to analysis through descriptive statistics and modeling of structural equations. The findings indicate the viability of the relationships between the constructs, so that each contributes to the composition of the research model and the Purchase Intention. Of the nine hypotheses tested, eight were statistically supported and structural and social paths were evidenced in the final model for which the Brazilian online consumer may intend to buy on Facebook. Among the contributions of the research results, it has been noticed that the influence of the Trust on the Intention to Purchase is enhanced by the online consumer experience and Social Support is one of the most relevant variables for the Brazilian users of Facebook in the adoption of social commerce. Finally, social media purchases such as Facebook are confirmed through the tools that allow user interaction, a positive experience and the generation of trust in transactional commitments established between the implicated parts in a virtual social network.